Surviving and Thriving in the Era of 4th Industrial Revolution: A View from the Trenches of the Indian Market - Roongta, Shrawankumar (SFIMAR Research Review, 2019)
Purpose: This research paper aims at reviewing and analysing the approach and strategies adopted by Indian firms to survive and thrive in the modern era of the fourth industrial revolution. Methodology: The paper is essentially exploratory in nature and undertakes a review of literature and analysis of secondary data, information and case studies to provide an insight into the strategies adopted by an Indian firm in the digital age. Findings/Conclusion: Indian manufacturing companies are keen to adopt digital technologies and have partnered with the world’s leading technology firms to transform their business functions. The digitisation efforts currently adopted focus on CRM and Supply Chain. There is much scope for companies in India to employ digitisation across their value chain to provide greater stakeholder value. Implications: The theme of the conference and this paper provides insights into the forces affecting and driving the businesses in the new era. Managerial implications include learning from firms in similar industries to adopt strategies to compete, co-operate and grow in the digital era. Originality: Few studies and research papers have aimed at analysing the strategies adopted by Indian firms to survive and thrive in the new era of digital transformation, this paper aims to contribute in that regards, and derives its originality in that context.